Psychological Literacy in Applied Psychology Disciplines: Back to, or Beyond, the Basics?. (April 2017) - Tomcho, Thomas J.; Foels, Rob
Undergraduate psychology majors need a broad base of knowledge in order to be viewed as competent graduates. In addition to acquiring basic knowledge, the American Psychological Association (APA) has guidelines for applied knowledge as well. In order to ensure a broad base of knowledge, teachers therefore need to know what the important psychological concepts are not only in both basic and applied areas of psychology. We examined key concepts across five applied areas of psychology and identified 30 key concepts that occur in two or more applied areas of psychology. It is evident from our findings that there is notable intersection between applied psychology and basic psychological science but also important applied concepts that stand alone from basic psychology. We discuss how these findings are directly relevant to APA's undergraduate learning goal of psychological literacy.